Pembuktian Tidak Langsung Dalam Praktik Kartel Pada Industri Minyak Goreng (Studi Putusan Nomor 24/KPPU-I/2009 Jo. Nomor 03/KPPU/2010/PN.Jkt.Pst Jo. Nomor 582k/Pdt.Sus/2011.) - Ulya, Rafa'any Darajatanti; Selian, Muhammad Ali Hanafiah; Rahmatullah, Indra (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2024)
This study aims to examine the application of indirect evidence in handling cartel practices in the cooking oil industry, focusing on a case study of Decision No. 24/KPPU-I/2009 Jo. No.03/KPPU/2010/PN.JKT.PST Jo. Number 582K/PDT.SUS/2011. The research method used is the juridical-normative approach, which relies on legal sources such as laws and regulations, legal principles, norms, principles, and expert opinions to analyze the issues studied. In the KPPU decision No. 24/KPPU-I/2009, the Business Competition Supervisory Commission (KPPU) stated that 21 cooking oil producers were proven to have practiced cartels. However, business actors applied with the Central Jakarta District Court, which then overturned the decision through Decision No. 03/KPPU/2010/PN.JKT.PST. The cancellation was based on the consideration that KPPU only relied on analysis, theories, and definitions considered speculative and not supported by substantial evidence. KPPU then filed an appeal to the Supreme Court, but the Supreme Court rejected the appeal and upheld the settlement of the first-level court through Decision No. 582K/PDT.SUS/2011. This study also highlights that challenges in indirect evidence can be overcome by implementing a leniency program, as has been implemented in various countries. This program incentivizes parties involved in the cartel to disclose information to the competition authority.